2010
DOI: 10.1002/fuce.201000034
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Channel‐to‐Channel Cross Convection in Serpentine Flow Fields

Abstract: Channel‐to‐channel cross convection in serpentine flow fields of polymer electrolyte fuel cells (PEFC) can influence the overall cell performance. The effect strongly depends on the gas transport properties of the gas diffusion layer (GDL). For the first time measured anisotropic, compression dependent permeability and effective diffusivity of GDLs are used to quantify the influence of cross convection on the local current distribution and performance. A model was developed to examine different channel‐rib geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 28 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, the cross-flow existed under several lands and the effect of changing the aspect ratio on the fuel cell performance became significant for the triple serpentine flow field. Tehlar et al [8] used a quasi-3D model to investigate the channel to channel pressure difference and the GDL compression effect for a serpentine flow field. They concluded that the cross-flow enhanced the overall current density and led to a more uniform current distribution.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the cross-flow existed under several lands and the effect of changing the aspect ratio on the fuel cell performance became significant for the triple serpentine flow field. Tehlar et al [8] used a quasi-3D model to investigate the channel to channel pressure difference and the GDL compression effect for a serpentine flow field. They concluded that the cross-flow enhanced the overall current density and led to a more uniform current distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This is since increasing the crosssection area of channel forces more air to flow through the fuel cell, and the water distribution is then more uniform through the catalyst layer. Tehlar et al [69] established an isothermal model to examine different channel-rib geometries and gas diffusion layer characteristics. Their results showed that cross convection in a serpentine channel can significantly increase the current density and consequently the power density of PEM fuel cells.…”
Section: Channel Configuration and Geometric Parametermentioning
confidence: 99%
“…Their results indicate that the trapezoidal cross-sectional shape ratio has a significant effect on the pressure variation in the flow field in both the presence and absence of cross over. The cross convection under the rib can significantly improve the performance and consequently the power density of PEFCs [19]. Experimental investigations on liquid water removal from gas diffusion layer by the cross flow have been carried out by Jiao et al [20].…”
Section: Introductionmentioning
confidence: 99%